Blending traditional and digital methods: enhancing EFL speaking skills beyond LMS platforms - Rehman, Naveed ur; Hajira, Bibi; Ahmed, Syed Naeem; Rehman, Shafiq ur (International Journal of Evaluation and Research in Education (IJERE), 2025)
The broad use of learning management system (LMS) in English as a foreign language (EFL) teaching indicates an increasingly urgent need for better methods to improve speaking skills. The research looks at the effectiveness of blended learning (BL) regarding fluency, pronunciation, and conversational improvement compared to the entire LMS approach within the learning process of EFL. It combines traditional face-to-face methods with digital tools to answer a significant need in language learning strategies. Therefore, the study compares the speaking proficiency of the two groups and investigates the impact of BL on motivation and engagement. The quasi-experimental design involved 100 intermediate EFL learners selected using purposive sampling from a Common European Framework of Reference for Languages (CEFR) A1–B2 English program. Following 12 weeks, the BL outperformed the LMS-only group in the post-test, showing development in fluency from 3.5 to 4.8 and pronunciation from 3.0 to 4.5. The LMS-only group revealed moderate gains but less pronounced: fluency increased from 3.4 to 4.0, and pronunciation from 3.1 to 3.8. Moreover, motivation and engagement increased in BL. This means combining traditional approaches with digital ones creates a more dynamic and robust environment for learning, which raises participation and proficiency in speaking. Further research is needed to optimize these strategies across various educational settings.